PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TEKNIK MAKE A MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 PAINAN KABUPATEN PESISIR SELATAN - Septiani, Grief; Delsi K, Delsi K; Haryono, Yulia (Pendidikan Matematika, 2014)
ABSTRACTThe research is based on the lack of mathematical concept comprehention by student of VIII grade SMPN 2 Painan and the not really fun atmosphere, like the strategy that applied by school is lack of variation, the purpose of the research is to determine wether mathematical concept comprehention student with cooperative education strategy make a match technique is good enough than students mathematical concept comprehention with applied conventional education to students of VIII grade SMPN 2 Painan. The kind of this research is experimental research. Instrument that used in this research is the last test with concept comprehention indicators. The test is an essay with reliability test is = 0,86. According to the analycis of data, we know that the two sample class are normal and homogen distribution. The result of hypothesis test using test by one side with the help of MINITAB software, we discovered P-value = 0.038, itâs mean the hypothesis the accepted. Therefore we can conclude that students comprehention concept with applied cooperative education strategy make a match is good than conventional education to students of VIII grade SMP N 2 Painan.